2017
DOI: 10.21873/anticanres.11551
|View full text |Cite
|
Sign up to set email alerts
|

The Kynurenine Pathway: A Primary Resistance Mechanism in Patients with Glioblastoma

Abstract: Abstract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 56 publications
(72 reference statements)
0
50
1
1
Order By: Relevance
“…Interestingly, indoleacetaldehyde, a product of tryptophan metabolism, was also shown to be putatively increased in the 8MGBA-TMZres media. Tryptophan metabolism disruption has been shown previously as a feature of treatment adaptation in GBM cells 15 . Consistent with our observation of increased extracellular vesicles, there was an increase in palmitic acid and stearic acid lipids in the GC-TOF-MS metabolites from the 8MBGA-TMZres cell line conditioned media ( Figure 6).…”
Section: Tmz Resistance Leads To An Increase In Intracellular Vesiclementioning
confidence: 80%
See 1 more Smart Citation
“…Interestingly, indoleacetaldehyde, a product of tryptophan metabolism, was also shown to be putatively increased in the 8MGBA-TMZres media. Tryptophan metabolism disruption has been shown previously as a feature of treatment adaptation in GBM cells 15 . Consistent with our observation of increased extracellular vesicles, there was an increase in palmitic acid and stearic acid lipids in the GC-TOF-MS metabolites from the 8MBGA-TMZres cell line conditioned media ( Figure 6).…”
Section: Tmz Resistance Leads To An Increase In Intracellular Vesiclementioning
confidence: 80%
“…This was reflected in the putative increase of lipids from the LC-MS analysis. Another hit, indoleacetaldehyde, is a product of tryptophan metabolism, hyperactivation of which occurs in GBM and is thought to suppress anti-tumor immunity 15 . Extracellular lipids, stearic and palmitic acid, were also found and validated in the GC-TOF-MS analysis along with citric acid.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of m 6 A is controversial in glioblastoma. Glioblastoma is an aggressive primary brain tumour in adults and has no significant improvement in survival rate so far 46. Previous studies strongly indicated the role of m 6 A methylation in self‐renewal and tumorigenesis of glioblastoma stem cells (GSCs) 47.…”
Section: The Dual Role Of M6a Modification In Human Cancersmentioning
confidence: 99%
“…Moreover, it is believed that curcumin has influence on the cells’ microenvironment. In fact, this drug changes the microenvironment around the cells to one that is harmful for proliferation of cancer cells, but conducive to healthy stem cells …”
Section: Resultsmentioning
confidence: 99%